Jalan Sosialisme Pasar Untuk Kebangkitan Tiongkok Sebagai Kekuatan Ekonomi Global: Dari Deng Xiaoping sampai Xi Jinping (1978-2013) - Zulfa Ainun Azhar; Luthfi Makhasin; Indaru Setyo Nurprojo (Jurnal Politikom Indonesiana, 2025)
China's rise as a global economic power cannot be separated from the implementation of market socialism initiated by Deng Xiaoping in 1978. However, the direction and sustainability of these reforms were crucially shaped by the 1989 Tiananmen Square protests, which served as a critical juncture that determined the relationship between political stability and economic liberalization. This article aims to analyze how the market socialism path developed across leaderships, from Deng Xiaoping to Xi Jinping, and how the post-Tiananmen policy path shaped China's position in the global political economy. This study uses qualitative methods with a Comparative Historical Analysis (CHA) approach to trace the historical cause-and-effect mechanisms and path dependence dynamics in China's political economy policies during the 1978-2013 period. The analysis is conducted using the theoretical framework of market socialism and global political economy, particularly the concept of performance legitimacy, to explain how economic growth has become the main source of political legitimacy. The results show that after Tiananmen, China strengthened political control while deepening market reforms through a pattern of selective adaptation to capitalist institutions. This combination enabled China to achieve rapid economic growth, maintain political stability, and consolidate its position as a global economic power without following the Western capitalist model. Keywords: Market Socialism, China, Deng Xiaoping, Global Political Economy, Comparative Historical Analysis